2002
DOI: 10.1128/aac.46.5.1253-1261.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Essential Residues in the Erm(B) rRNA Methyltransferase ofClostridium perfringens

Abstract: Macrolide-lincosamide-streptogramin B resistance is widespread, with the determinants encoding resistance to antibiotics such as erythromycin being detected in many bacterial pathogens. Resistance is most commonly mediated by the production of an Erm protein, a 23S rRNA methyltransferase. We have undertaken a mutational analysis of the Erm(B) protein from Clostridium perfringens with the objective of developing a greater understanding of the mechanism of action of this protein. A recombinant plasmid that carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…An antibody against C. perfringens ErmB (52) was used to probe the expression level of ErmB. A catalytically inactive mutant of ErmB (Y103A, Y104 numbering in ErmC [65]) served as a control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An antibody against C. perfringens ErmB (52) was used to probe the expression level of ErmB. A catalytically inactive mutant of ErmB (Y103A, Y104 numbering in ErmC [65]) served as a control.…”
Section: Resultsmentioning
confidence: 99%
“…Total soluble proteins (40 μg/lane) were resolved using 4 to 20% TGX SDS-PAGE (Bio-Rad), and the proteins were transferred to a nitrocellulose membrane using a Trans-Blot Turbo system (Bio-Rad). A 1/1,000 dilution of anti-ErmB (kindly provided by J. Rood) (52) and a 1/10,000 dilution of anti-RNAP α (NeoClone) were used for immunoblotting. The intensity of immunoblot bands was quantitated by using ImageJ.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed that macrolides (azithromycin, clarithromycin) are potent agents against some anaerobic bacteria, although their bacteriostatic effects hinder their usefulness in serious infections. Resistance to the macrolide-lincosamide-streptogramine-group of antimicrobials manifest uniformly (which can be attributed to various erm genes): due to the methylation of two specific adenine residues of the 23S rRNA, the effective binding of the drugs to ribosome is prevented [ 159 , 160 , 161 , 162 , 163 ].…”
Section: Antibiotic Resistance In Anaerobic Bacteria: the Importanmentioning
confidence: 99%
“…Although motif X, one of the nine common SAM-dependent MTase functional motifs, motifs I to VIII and X observed in amino (N 4 -cytosine or N 6 -adenine) MTases [ 18 ] is well known to be located before motif I in Erm and KsgA/Dim1, its identity, especially the range of sequence encompassing motif X, is different depending on the report. It ranged from 18 amino acids [ 19 ], 6 amino acids [ 37 ] to 4 amino acids [ 17 ] (GQNF is the most appeared amino acids). Residue V21 in M .…”
Section: Discussionmentioning
confidence: 99%
“…In ErmC’ and ErmB, the motif X sequence is located near the active site and presumably, each amino acid might perform more than just one role. The exact location and range of motif X in Erm proteins are somewhat different depending on the reports [ 17 , 19 , 20 ]. However, in that motif, some consensus G(S/T)-Q-N(H)-F(L, Y) in which Q is highly conserved among almost all members of the families of Erm, and another sequence might be altered to amino acid(s) in parenthesis, could be identified with Erm families and some other slight variation in that consensus could be found with KsgA/Dim1 (see below).…”
Section: Introductionmentioning
confidence: 99%